Uma simulação do espalhamento do Zika vírus na Flórida - Costa, Bruno Lucian Gonçalves da (2017)
Some cases of Zika occurred in the southern states of the USA bordering on the Gulf of Mexico (Florida, Louisiana & Texas) because these states have a suitable hot & wet climate and the vector, Aedes Aegyptus mosquitos. This project uses two standard mathematical models for epidemics (SIR: susceptible, Infected, recovered and SEIR: susceptible, exposed, infected, recovered) developed by McKendrick & Kermach to simulate the propagation within the state of Florida. To do this, we collected Demographic data from the US census on 67 towns in Florida Data on migrations from one town to another (also from the US Census) Weekly reports on the number of cases of Zika obtained by webscrapping the Florida Health Service. The Epigrass program developed by Fiocruz was used to simulate the evolution of the Zika epidemic week by week from February to the end of July 2016, for both the SIR and the SEIR models. From this we constructed the propagation dendrograms assuming that propagation started simultaneously in three cities: Miami-Dade, Hillsborough and Lee.